2018
DOI: 10.1002/ddr.21469
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and antifungal activity of novel cinnamon–pyrazole carboxamide derivatives

Abstract: Hit, Lead & Candidate Discovery To discover succinate dehydrogenase inhibitors with a novel structure, we introduced cinnamic acid structure to optimize the lead structure 1 and synthesized four series of cinnamon–pyrazole carboxamide derivatives. The bioassay data showed that compounds (E)‐N‐(1‐[4‐chlorophenyl]‐4‐cyano‐1H‐pyrazol‐5‐yl)‐3‐(2‐fluorophenyl) acrylamide (5III‐d) and (E)‐3‐(2‐chlorophenyl)‐N‐(1‐[4‐chlorophenyl]‐4‐cyano‐1H‐pyrazol‐5‐yl) acrylamide (5III‐f) showed the significant antifungal activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…1). 15,16 At present, five commercial SDHI fungicides have been successfully developed by structural modification of the amide bridge, including isofetamid, 17 fluopyram, 18 pydiflumetofen, 19 isoflucypram 20 and pyrapropoyne. 21 Fluopyram (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…1). 15,16 At present, five commercial SDHI fungicides have been successfully developed by structural modification of the amide bridge, including isofetamid, 17 fluopyram, 18 pydiflumetofen, 19 isoflucypram 20 and pyrapropoyne. 21 Fluopyram (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, five‐ and six‐membered heterocyclic systems are motifs of many efficacious drugs (Figure ). Pyrazoles are well‐known examples of aromatic five‐membered heterocyclic organic compounds containing two adjacent nitrogen atoms endowed with diverse biological activity on humans such as antimicrobial (Sridhar et al, ), antidiabetic, anticancer (Altıntop, Ozdemir, Ilgın, & Atli, ), anti‐inflammatory (Raffa et al, ; Ren et al, ), antiviral (El‐Sabbagh et al, ), anticonvulsant, and antidepressant (Abdel‐Aziz, El‐Din, Abuo‐Rahma, & Hassan, ). Furthermore, the pyrazole derivatives are used as synthon for the development of condensed heterocyclic scaffolds and thus signify as interesting template for combinational chemistry (Singh, Paul, & Holzer, ; Tiwari, Ameta, Ranwal, Ameta, & Punjabi, ).…”
Section: Introductionmentioning
confidence: 99%
“…The study showed that methylcellulose also played a role in CA retention in the tongue tissue of the Candida ‐infected mouse, while CA was not detected in blood, thus indicating materials, such as methylcellulose, could also be used as a tool for the treatment of local (oral) candidiasis . The cinnamic acid moiety has been used / introduced further into the lead structure of other candidate compounds to develop succinate dehydrogenase inhibitor for fungal treatment …”
Section: Resultsmentioning
confidence: 99%
“…25 The cinnamic acid moiety has been used / introduced further into the lead structure of other candidate compounds to develop succinate dehydrogenase inhibitor for fungal treatment. 26 Collectively, studies indicated the important role of hydrocarbon side chain of CA for high-potency antifungal activity. Elucidation of precise structure-activity relationship of test compounds for their antifungal efficacy in different food matrices warrants future investigation.…”
Section: Effect Of Phs On Antifungal Activity Of Og Ca and 2h5mmentioning
confidence: 99%